"It's what midwifery is all about": Western Australian midwives' experiences of being 'with woman' during labour and birth in the known midwife model - Bradfield, Zoe; Hauck, Yvonne; Kelly, Michelle; Duggan, Ravani (BioMed Central Ltd, 2019)
Background: The phenomenon of being 'with woman' is fundamental to midwifery as it underpins its philosophy, relationships and practices. There is an identified gap in knowledge around the 'with woman' phenomenon from the perspective of midwives providing care in a variety of contexts. As such, the aim of this study was to explore the experiences of being 'with woman' during labour and birth from the perspective of midwives' working in a model where care is provided by a known midwife. Methods: A descriptive phenomenological design was employed with ten midwives working in a 'known midwife' model who described their experiences of being 'with woman' during labour and birth. The method was informed by Husserlian philosophy which seeks to explore the same phenomenon through rich descriptions by individuals revealing commonalities of the experience. Results: Five themes emerged 1) Building relationships; 2) Woman centred care; 3) Impact on the midwife; 4) Impact on the woman; and 5) Challenges in the Known Midwife model. Midwives emphasised the importance of trusting relationships while being 'with woman', confirming that this relationship extends beyond the woman - midwife relationship to include the woman's support people and family. Being 'with woman' during labour and birth in the context of the relationship facilitates woman-centred care. Being 'with woman' influences midwives, and, it is noted, the women that midwives are working with. Finally, challenges that impact being 'with woman' in the known midwife model are shared by midwives. Conclusions: Findings offer valuable insight into midwives' experiences of being 'with woman' in the context of models that provide care by a known midwife. In this model, the trusting relationship is the conduit for being 'with woman' which influences the midwife, the profession of midwifery, as well as women and their families. Descriptions of challenges to being 'with woman' provide opportunities for professional development and service review. Rich descriptions from the unique voice of midwives, provided insight into the applied practices of being 'with woman' in a known midwife model which adds important knowledge concerning a phenomenon so deeply embedded in the philosophy and practices of the profession of midwifery.